Nike Training Club Applications To Improve Football Learning In The Independent Era Of Learning On Students Of Penjas FKIP UNIB - Bogy Restu Ilahi; Septian Raibowo; Tono Sugihartono; Fina Hiasa (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
Research on Nike Training Club Applications to Improve Football Learning in the Free Era of Learning for Physical Education Students Fkip Unib aims to improve soccer learning for physical education students at Fkip Unib using the Nike training club (NTC) application. The method used in this study is (Classroom Action Research), the results of this study are descriptive because in this study a description will be produced about the extent to which handball learning is improved by using the Nike Training Club (NTC) application for physical education students FKIP UNIB. The sample of this research is the third semester students of Physical Education Study Program, totaling 24 people. The data analysis technique used in this study is descriptive statistics in the form of percentages presented in tables or graphs. The results of this study are students can improve learning in soccer courses, this can be seen from the percentage results which show that during the pre-cycle they get an average score. -an average of 59, with 4 students getting a complete score getting a percentage of 16.70%. In the first cycle, the average score was 67.50 with 12 complete students getting a percentage of 46%. And in cycle II, it showed significant results with completeness reaching 20 students out of 24 students with an average score of 74, getting a percentage of 84%. from these results indicate that the learning outcomes of the physical education study football subject increased after learning using adobe flash was applied.